Facile synthesis and gas sensing properties of nanotriangular tin oxide - Deshmukh, Rupali G.; Badadhe, Satish S.; Vaishampayan, Mukta V.; Mulla, Imtiaz S. (Materials Letters, 2008)
In the present study we report a simple and convenient chemical route using pentaerythritol as a structure-directing agent for the synthesis of crystalline nanotriangular SnO2. We propose the scheme for the formation of nanotriangular structures wherein the preliminary spherical nanocrystallites are formed due to the low surface energy associated with them. These spherical nanocrystallites grow into the various linear intermediate shapes like Y, bi and tripods, which finally lead to the triangles, pyramids and bipyramids. Such variation in the structure occurs due to the structure directing pentaerythritol. These polycrystalline SnO2 nanomaterials with structural peculiarities were tested for the gas sensing characteristics. Their response towards ethanol vapor, H-2 and LPG were investigated. It was found to exhibit high response towards ethanol vapors at the operating temperature of 250 degrees C. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Nanomaterials; Oxides; Semiconductors; sensors

Fe-doped SnO(2) nanomaterial: a low temperature hydrogen sulfide gas sensor - Vaishampayan, Mukta V.; Deshmukh, Rupah G.; Walke, Pravin; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2008)
The effect of Fe-doping on the surface chemistry and gas-sensing properties of nanocrystalline tin oxide is analyzed. The pristine and Fe-doped SnO(2) are synthesized by the modified Pechini citrate route that produces around 40 and 18 nm sized nanoparticles, respectively. 1 at.% Fe-doped SnO(2) shows significantly high selectivity towards hydrogen sulfide gas with capability to detect even 10 ppm of hydrogen sulfide at room temperature, with change of about one order of magnitude in the resistance within 5-15 s. In comparison, pristine SnO(2) shows negligible response towards H(2)S at room temperature. The ideal response and recovery of Fe-doped SnO(2) at low concentration of gas suggests Fe-doped SnO(2) nanomaterial as a potential low cost, low temperature H(2)S gas sensor. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Fe-doping; H(2)S; nanomaterial; Sensor; tin oxide

Influence of Pd doping on morphology and LPG response of SnO2 - Vaishampayan, Mukta V.; Deshmukh, Rupali G.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2008)
In the present study nanocrystalline pristine and Pd-doped SnO2 (Pd:SnO2) with various mol% Pd have been synthesized by a modified Pechini citrate route. Transmission electron microscopy and X-ray powder diffraction studies were used to characterize the morphology, crystallinity, and structure of the SnO2 and Pd:SnO2. The response of the pristine SnO2 and Pd:SnO2 was studied towards different reducing gases. The 1.5 mol% Pd doping showed an enhanced response of 75 and 95% towards LPG at as low as 50 and 100 degrees C, respectively, which were quite large high value as compared with pristine SnO2 (38 and 35% at 50 and 100 degrees C, respectively). Structural characterization revealed that Pd doping reduced the crystallite size of SnO2 and helps in the formation of distinct spherical nanospheres at a calcinations temperature of 500 degrees C. Thus the increase in LPG response can be correlated with the spherical morphology, a decrease in the crystallite size (11 nm) due to doping with Pd as compared with the pristine SnO2 (26 nm) and main role of Pd as a catalyst. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: LPG sensor; nanospheres; palladium doping; tin oxide

Preparation of ferroelectric CaBi(4)Ti(4)O(15) powders from novel hydroxide precursors - Deshmukh, Rupali G.; Vaishampayan, Mukta V.; Darshane, Sonali L.; Mulla, Imtiaz S.; Gaikwad, A. B.; Rao, N. Kotaserwara; Ravi, V. (Materials Letters, 2008)
Ferroelectric CaBi(4)Ti(4)O(15) (CBT) powders were prepared for the first time from their respective hydroxides. Commercially purchased Ca(OH)(2) is mixed thoroughly with freshly prepared Bi(OH)(3) and Ti(OH)(4) in stoichiometrie ratio and heated at different temperatures ranging from 100 to 600 degrees C. The CBT phase found to be formed at 500 degrees C by the X-ray diffraction studies. This is the lowest temperature so far reported in the literature for the formation of CBT phase. The advantage of this method is that it also avoids the formation of calcium carbonate phase during synthesis. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD) method. The average particle size and morphology were studied by scanning electron microscopy (SEM) technique. (c) 2007 Elsevier B.V All rights reserved.
Keywords: CaBi(4)Ti(4)O(15); Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods

Low temperature pH dependent synthesis of flower-like ZnO nanostructures with enhanced photocatalytic activity - Vaishampayan, Mukta V.; Mulla, Imtiaz S.; Joshi, Satyawati S. (Materials Research Bulletin, 2011)
In the present study we have synthesized flower-like ZnO nanostructures comprising of nanobelts of 20 nm width by template and surfactant free low-temperature (4 degrees C) aqueous solution route. The ZnO nanostructures exhibit flower-like morphology, having crystalline hexagonal wurtzite structure with (001) orientation. The flowers with size between 600 and 700 nm consist of ZnO units having crystallite size of similar to 40 nm. Chemical and structural characterization reveals a significant role of precursor: ligand molar ratio, pH, and temperature in the formation of single-step flower-like ZnO at low temperature. Plausible growth mechanism for the formation of flower-like structure has been discussed in detail. Photoluminescence studies confirm formation of ZnO with the defects in crystal structure. The flower-like ZnO nanostructures exhibit enhanced photochemical degradation of methylene blue (MB) with the increased concentration of ligand, indicating attribution of structural features in the photocatalytic properties. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Defects; Nanostructures; Optical properties; Semiconductor

Optical and photocatalytic properties of single crystalline ZnO at the air-liquid interface by an aminolytic reaction - Vaishampayan, Mukta V.; Mulla, Imtiaz S.; Joshi, Satyawati S. (Langmuir, 2011)
Crystalline flowerlike ZnO was synthesized by an aminolytic reaction at the air-liquid interface in an aqueous media at an alkaline pH. A thin visible film was formed at the air-liquid interface by self-assembly of flowerlike ZnO. Diffraction studies show rearrangement of the single crystalline units at the air-liquid interface leading to the formation of nanobelts. These nanobelts overlap systematically to form petals of the flowerlike structure; individual petals get curved with time. Each nanobelt is found to be single crystalline and can be indexed as the hexagonal ZnO phase. The organic product formed in the aminolytic reaction and dissolution-reprecipitation mechanism is the driving force for the formation of flowerlike ZnO at the air-liquid interface. A clear relationship between the surface, photocatalytic, and photoluminescent properties of ZnO is observed. The flowerlike structure exhibits a blue shift (3.56 eV) in the band emission as compared to bulk ZnO (3.37 eV). The photodegradation of methylene blue over the flowerlike ZnO catalyst formed at the air-liquid interface and in the sediments shows enhanced photocatalytic activity. The sub-bands formed due to surface defects facilitate separation of charge carriers increasing their lifetime, leading to enhanced photocatalytic activity of flowerlike ZnO.

Synthesis and electrochemistry of pseudocapacitive multilayer fullerenes and MnO2 nanocomposites (vol 2, pg 2152, 2014) - Azhagan, Muniraj Vedi Kuyil; Vaishampayan, Mukta V.; Shelke, Manjusha V. (Journal of Materials Chemistry A, 2014)

Synthesis and electrochemistry of pseudocapacitive multilayer fullerenes and MnO2 nanocomposites - Azhagan, Muniraj Vedi Kuyil; Vaishampayan, Mukta V.; Shelke, Manjusha V. (Journal of Materials Chemistry A, 2014)
Electrode materials with efficient capabilities for ionic and electronic transport are key to high performance supercapacitors. Here, we demonstrate a simple and comparatively low temperature synthesis of functionalized multilayer fullerenes so called carbon nano-onions (CNOs) as the electrode for high performance electrochemical supercapacitors. The exohedral type supercapacitor formed due to nonporous CNOs showed higher specific capacitance than conventional graphitic/mesoporous/activated carbons. Surface redox functionalities of these CNOs add up to significant pseudocapacitance. Further in situ incorporation of MnO2 nanoparticles to these CNOs increased the specific capacitance up to 1207 F g(-1), which is close to the theoretical value of pseudocapacitive MnO2.